Estimated glomerular filtration rate is a marker of mortality in the European Scleroderma Trials and Research Group (EUSTAR) database - Gigante, Antonietta; Hoffmann-Vold, Anna-Maria; Fegatelli, Danilo Alunni; Gabrielli, Armando; Leodori, Giorgia; Coleiro, Bernard; De Santis, Maria; Dagna, Lorenzo; Alegre-Sancho, Juan Jose; Montecucco, Carlomaurizio; Carreira, Patricia E.; Balbir-Gurman, Alexandra; et al. (Rheumatology, 2022)
Objectives. The study aim was to evaluate the estimated glomerular filtration rate (eGFR), its association with clinical disease and its predictive ability with respect to mortality in SSc patients from the European Scleroderma Trials and Research Group (EUSTAR) database.
CRIS-Team WoS Importer:2022-02-18